How Do Patients Know - Kukla, Rebecca (The Hastings Center report, 2007)
The way patients make health care decisions is much more complicated than is often recognized. Patient autonomy allows both that patients will sometimes defer to clinicians and that they should sometimes be active inquirers, ready to question their clinicians and do some independent research. At the same time, patients' active inquiry requires clinicians' support.